Hippocampal vascular supply and its mediating role in systemic physiological influences on hippocampal volume - Kim, Tae; Rasero, Javier; Marsland, Anna L.; Scudder, Mark R.; Ibrahim, Tamer S.; Gianaros, Peter J. (Frontiers in Aging Neuroscience, 2025)
BackgroundAging-related systemic cardiovascular changes can impair cerebrovascular circulation, contributing to hippocampal atrophy and cognitive decline. However, the mechanistic pathways by which systemic alterations may relate to hippocampal atrophy via hippocampal vascular features remain unclear.MethodsIn this study, 191 participants (aged 30–59 years, 115 female) underwent 7T MRI to segment hippocampal supply vessels and hippocampal volume from T1-weighted images. Twenty-three systemic parameters related to the metabolic syndrome, autonomic function, inflammation, vascular stiffness, and endothelial function were measured at rest. Mediation analysis examined whether hippocampal vessel velocity and size mediated the relationship between systemic factors and hippocampal volume.ResultsHippocampal volume was highly associated with hippocampal supply vessel velocity, showing a pronounced right lateralized effect. Indirect associations of vessel velocity with hippocampal volume were identified for circulating vascular and intercellular adhesion molecules, heart rate variability, fasting insulin, and spontaneous baroreflex sensitivity. No significant mediated relationships were found for blood pressure, adiposity, mean heart rate, cardiac output, pre-ejection period, reactive hyperemia, pulse wave velocity, mean carotid artery intimal medial thickness, fasting glucose, lipid levels, circulating interleukin-6, hemoglobin A1C, or blood pressure variability.ConclusionThese findings highlight the role of vascular inflammation, autonomic dysfunction, and metabolic disturbances in hippocampal atrophy, with hippocampal vessel velocity serving as a key mediator. This insight advances our understanding of cerebrovascular contributions to hippocampal structural integrity and cognitive health.